2008
DOI: 10.1080/00071660802295183
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathomorphological, serum biochemical and histological studies in broilers fed ochratoxin A and a toxin deactivator (Mycofix® Plus)

Abstract: 1. Toxic effects of two concentrations (0.5 and 1 mg/kg) of ochratoxin A (OTA) and attenuating effects of a toxin deactivator (Mycofix Plus(MTV INSIDE)) containing the yeast Trichosporon mycotoxinivorans on the performance (feed conversion ratio; body weight gain), serum enzymes (lactate dehydrogenase, gamma-glutamyltranspeptidase and aspartate aminotransferase) and clinico-pathomorphology of internal organs were studied in 270 one-day-old broiler chicks divided into 9 groups over a 42-d period. 2. Feed conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 20 publications
13
29
1
Order By: Relevance
“…A similar effect on broiler chick immune system organ weights-due to ochratoxicosis-was reported by Dwivedi and Burns (1984), Hanif et al (2008), and Awaad et al (2011). Feeding an OTA-contaminated (0.4 and 0.8 mg/Kg diet) diet to male broiler chicks from the day after hatching to 5 weeks-of-age resulted in the significant decrease in thymus weight (Elaroussi et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
“…A similar effect on broiler chick immune system organ weights-due to ochratoxicosis-was reported by Dwivedi and Burns (1984), Hanif et al (2008), and Awaad et al (2011). Feeding an OTA-contaminated (0.4 and 0.8 mg/Kg diet) diet to male broiler chicks from the day after hatching to 5 weeks-of-age resulted in the significant decrease in thymus weight (Elaroussi et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
“…Unfortunately, the literature is lacking information about the effect of in ovo OTA on the body and relative organ weights of developing chicks. However, studies made on OTA-fed chicks reported an increase in the weights of liver and kidneys (Hanif et al 2008;Stoev et al 2002) and a decrease in weights of bursa of Fabricius (Singh et al 1990;Gibson et al 1989). This increase in the weights of liver and kidneys is correlated with nephro-and hepatotoxic effects of OTA, resulting in the accumulation of inflammatory cells (Zahoor-ul-Hassan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A feed additive named Mycofix® Plus contains T. mycotoxinivorans , mycotoxin adsorbents upgraded by the addition of epoxidase and lactonase activities, and is successfully used in broilers to counteract the toxic effects of OTA [236]. …”
Section: Prevention Of Toxic Effects Of Otamentioning
confidence: 99%